Proverbs and identity: a study of Hadoti proverbs - Dwivedi, Amitabh Vikram (2015)
DWIVEDI, Amitabh Vikram. Proverbs and identity: a study of Hadoti proverbs. Revista Entrepalavras, Fortaleza, ano 5, v. 5, n. 1, p. 8-19, jan./jun. 2015.